2014
DOI: 10.1590/0004-282x20140120
|View full text |Cite
|
Sign up to set email alerts
|

Brain regions supporting verbal memory improvement in healthy older subjects

Abstract: Despite growing interest in developing cognitive training interventions to minimize the aging cognitive decline process, no studies have attempted to explore which brain regions support the application of semantic strategies during verbal memory encoding. Our aim was to investigate the behavioral performance and brain correlates of these strategies in elderly individuals using fMRI in healthy older subjects. Method: Subjects were scanned twice on the same day, before and after, directed instructions to apply s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
15
0
2
Order By: Relevance
“…In a number of prior studies (e.g., Wagner et al, 1998; Savage et al, 2001; Paller and Wagner, 2002; Addis and McAndrews, 2006; Kirchhoff and Buckner, 2006; Miotto et al, 2006), activation of left inferior prefrontal regions during encoding in young adults has been associated with the use of effective semantic strategies, as well as with a concomitant increase in performance on a subsequent memory test. More recent work (Kirchhoff et al, 2012; Miotto et al, 2014) has shown that older adults who are trained to engage semantic encoding strategies also show increased activity in left IFG, among other regions, during encoding. It is notable that when we compare the six activation peaks in left IFG from across those two studies (transformed from Talairach to MNI space as necessary; Lancaster et al, 2007) with our whole-brain analysis examining the correlation between value effects during encoding and selectivity index (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of prior studies (e.g., Wagner et al, 1998; Savage et al, 2001; Paller and Wagner, 2002; Addis and McAndrews, 2006; Kirchhoff and Buckner, 2006; Miotto et al, 2006), activation of left inferior prefrontal regions during encoding in young adults has been associated with the use of effective semantic strategies, as well as with a concomitant increase in performance on a subsequent memory test. More recent work (Kirchhoff et al, 2012; Miotto et al, 2014) has shown that older adults who are trained to engage semantic encoding strategies also show increased activity in left IFG, among other regions, during encoding. It is notable that when we compare the six activation peaks in left IFG from across those two studies (transformed from Talairach to MNI space as necessary; Lancaster et al, 2007) with our whole-brain analysis examining the correlation between value effects during encoding and selectivity index (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, interventional programmes based on CI and PE frequently last from several months to one year, which would be a time period more than sufficient to promote the activation of neuroplasticity mechanisms. Nevertheless, neural activity changes have also been observed after one or only a few sessions of CT in healthy elderly subjects (Belleville et al, 2011;Kirchhoff et al, 2012;Miotto et al, 2014;Nyberg et al, 2003) and cognitively impaired patients (Belleville et al, 2011;Hampstead et al, 2011;Hampstead et al, 2012a). Likewise, neural activity changes have been observed after a single session or only a few sessions of TMS or tES in healthy elderly subjects (Holland et al, 2011;Lindenberg et al, 2013;Sole-Padulles et al, 2006) and cognitively impaired patients (Devi et al, 2014;Khedr et al, 2014;Meinzer et al, 2014).…”
Section: Relationships Among Cognitive Improvement Neural Changes Anmentioning
confidence: 99%
“…Instructing or training older adults to use elaborative encoding strategies can increase their use of those strategies and improve their memory performance (Kirchhoff et al, 2012; Miotto et al, 2014; Naveh-Benjamin et al, 2007). Thus, age differences in spontaneous encoding strategy use are most likely due to age differences in the ability to self-initiate complex effortful strategies rather than impairment in older adults’ ability to effectively use them.…”
Section: Introductionmentioning
confidence: 99%